 JMAP

141 questions
2 followers

F'(x) = -2/x, f(2) = -2ln2

f'(x) = -2/x, f(2) = -2ln2

A) f(x) = -ln- x + 3, x < 0

B) f(x) = -2lnx + 2, x > 0

C) f(x) = -2lnx, x > 0

D) f(x) = -ln-x - 1, x < 0

Tags: JMAP, math, differential-equation

F'(x) = -1/x, f(3) = -ln(3) -1

f'(x) = -1/x, f(3) = -ln(3) -1

A) f(x) = -3lnx - x, x < 0

B) f(x) = 2lnx + 1, x > 0

C) f(x) = -2lnx - x + 3, x < 0

D) f(x) = -lnx - 1, x > 0

Tags: JMAP, math, differential-equation

F'(x) = 1/x^2, f(-1) = -1

f'(x) = 1/x2, f(-1) = -1

A) f(x) = -1/2x4 + 2, x < 0

B) f(x) = -1/x - 2, x < 0

C) f(x) = 1/x - 2, x < 0

D) f(x) = -1/x2 + 2, x < 0

Tags: JMAP, math, differential-equation

F'(x) = -1/x^5, f(-1) = -7/4

f'(x) = -1/x5, f(-1) = -7/4

A) f(x) = -1/x2 - 2, x < 0

B) f(x) = -3/x, x > 0

C) f(x) = 1/4x4 - 3, x > 0

D) f(x) = 1/4x4 - 2, x < 0

Tags: JMAP, math, differential-equation

Dy/dx = -2x - 1, y(-1) = -1

dy/dx = -2x - 1, y(-1) = -1

A) y = 2x2 + 3x + 3

B) y = x2 + 2x + 1

C) y = x2 + x - 2

D) y = -x2 - x - 1

Tags: JMAP, math, differential-equation

Dy/dx = 4x + 2, y(0) = 0

dy/dx = 4x + 2, y(0) = 0

A) y = 2x2 + 2x

B) y = 2x2 + 3x - 3

C) y = -2x2 + 3x + 1

D) y = 2x2 + x

Tags: JMAP, math, differential-equation

Dy/dx = 4x - 3, y(1) = 0

dy/dx = 4x - 3, y(1) = 0

A) y = 2x2 + x - 1

B) y = -x2 + x - 2

C) y = 2x2 + x + 1

D) y = 2x2 - 3x + 1

Tags: JMAP, math, differential-equation

Dy/dx = -2x + 3, y(3) = 3

dy/dx = -2x + 3, y(3) = 3

A) y = x2 + 3x + 1

B) y = x2 + 2x - 2

C) y = -x2 + 3x + 3

D) y = x2 + 2x + 1

Tags: JMAP, math, differential-equation

Complete: “To evaluate an expression with a variable, you... .”

Complete: “To evaluate an expression with a variable, you... .”